Kegiatan Pelayanan Posyandu pada bayi dan balita di Desa Kolisia, Kecamatan Magepanda-Kabupaten Sikka - Ringgi Kuwa, Maria Kornelia; Eda, Laurentina Nona; Wela, Yustina; Lito, Petronela; Manue, Karlina S. S; Pela, Yustinus; Wa’a, Faleria A S. Ruing (PPPM Stikes Banyuwangi, 2022)
Abstract: Background: The use of weighing toddlers in Posyandu is influenced by the knowledge of cadres, motivation of cadres, and work factors of mothers of children under five. Facilitating the community to build a community alert system in an effort to overcome emergency situations from non-clinical aspects related to pregnancy and work is one of community empowerment in the MCH sector through regular Posyandu activities. Maternal and child health assessments are carried out through Posyandu activities. Method: This activity uses a mentoring intervention method for students together with posyandu cadres, and nursing partners at the Magepanda Health Center together to carry out activities at the Posyandu. The mentoring method is divided into the preparation stage, the work stage, the termination stage, and the documentation evaluation stage. Result: This activity was carried out in the working area of ​​the Posyandu, Kolisia Village, Magepanda Village Health Center, Sikka Regency. Posyandu activities carried out in 5 posyandu in Kolisi village with a target number of 178 infants and toddlers, but in Posyandu activities 166 people (93.25%) came, while 12 people did not come to Posyandu (7.22%). In SDIDTK activities, there are several activities, including KPSP which was carried out on 111 toddlers. KMPE as many as 30 toddlers, M-chat as many as 35 people, GPPH as many as 28 toddlers. Conclution: Suggestions for health workers, especially Posyandu cadres and managers, are expected to remain active, communicative and disciplined in assisting and providing health services for the community.